2018
DOI: 10.1519/jsc.0000000000002324
|View full text |Cite
|
Sign up to set email alerts
|

Validity of an Isometric Midthigh Pull Dynamometer in Male Youth Athletes

Abstract: Till, K, Morris, R, Stokes, K, Trewartha, G, Twist, C, Dobbin, N, Hunwicks, R, and Jones, B. Validity of an isometric midthigh pull dynamometer in male youth athletes. J Strength Cond Res 32(2): 490-493, 2018-The purpose of this study was to investigate the validity of an isometric midthigh pull dynamometer against a criterion measure (i.e., 1,000-Hz force platform) for assessing muscle strength in male youth athletes. Twenty-two male adolescent (age 15.3 ± 0.5 years) rugby league players performed 4 isometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Our portable IMTP system was selected to improve the accessibility of isometric assessments, given the cost and ungainly nature of force‐plate systems. However, while similar systems provide accurate F max with some systematic bias, 34‐37 the one report of RFD validity that exists depicts poor agreement compared to fixed‐bar force‐plate systems 35 . Our system overcomes several critical limitations of previous designs that feasibly improve RFD accuracy (eg, rigid base‐plate [wood vs reinforced steel], high sampling frequency [< 100 vs 1000 Hz], and rigid tether [material lashing strap vs hardened metal chain]), and might be considered a different assessment than the criterion solution since they are fixed vs open chain.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our portable IMTP system was selected to improve the accessibility of isometric assessments, given the cost and ungainly nature of force‐plate systems. However, while similar systems provide accurate F max with some systematic bias, 34‐37 the one report of RFD validity that exists depicts poor agreement compared to fixed‐bar force‐plate systems 35 . Our system overcomes several critical limitations of previous designs that feasibly improve RFD accuracy (eg, rigid base‐plate [wood vs reinforced steel], high sampling frequency [< 100 vs 1000 Hz], and rigid tether [material lashing strap vs hardened metal chain]), and might be considered a different assessment than the criterion solution since they are fixed vs open chain.…”
Section: Discussionmentioning
confidence: 95%
“…Athletes performed the IMTP using a portable dynamometer consisting of an Olympic lifting bar with its ends and bearings removed (7.5 kg), attached to a rigid platform via a heavy‐duty chain (see Figure 1). The portable system is a more advanced alternative to those presented in the literature, 34‐37 which have provided acceptable measurement of peak force capacities but limited and mixed results for RFD (discussed in the limitations) 35 . For the test, the athletes were instructed to set themselves in a position where they felt comfortable to present maximum effort (ie, like that of the second pull of the “clean‐pull” movement, commonly used by alpine skiers 14 and other athletes).…”
Section: Methodsmentioning
confidence: 99%
“…To assess muscular strength, the IMTP was performed using a dynamometer (T.K.K.5402, Takei Scientific Instruments Co. Ltd, Niigata, Japan) sampling at 122 Hz, which was attached to a wooden platform, a chain and a latissimus pulldown bar. The test protocol outlined by Till et al, (2018) was utilised in which participants were positioned by standing with their feet approximately shoulder width apart with the chain length adjusted so that the bar was positioned at the mid-thigh. Participants were instructed to maintain a flat back position with their head up and arms straight.…”
Section: Methodsmentioning
confidence: 99%
“…While peak force was reported as highly reliable with a conventional force platform (ICC 0.88, CV 9.2% and ICC 0.96, CV 3.10% respectively), the rate of force development and force at selected time points did not reach acceptable levels of reliability compared to the force platform (ICC ≤ 0.31, CV ≥ 17.3% and ICC ≤ 0.31, CV ≥ 16.2%, respectively) (James et al, 2017). Similarly, research using a custom built IMTP dynamometer against a criterion measure (i.e., 1,000-Hz force platform) for assessing muscle strength in male youth rugby league athletes (Till et al, 2018) reported underestimated peak force and peak force/body mass obtained using a criterion force platform, but with strong correlations between the dynamometer and the force platform. While single load cells and dynamometers can be used to quantify peak forces, other variables such as force, impulse and rate of force development, require force plates to offer more in-depth analysis of physical qualities at the recommended sampling frequency of 1000 Hz (Bartlett, 2007).…”
Section: Introductionmentioning
confidence: 99%